Sovereign credit risk and stock markets: Does the markets' dependency increase with financial Distress? - Paulo Pereira da Silva (International Journal of Financial Studies, 2014)
This paper addresses the relationship between stock markets and credit default swaps (CDS) markets. In particular, I aim to gauge if the co-movement between stock prices and sovereign CDS spreads increases with the deterioration of the credit quality of sovereign debt. The analysis of correlations, Granger causality, cointegration, and the results of an error-correction model represented in a state space form show a close link between these markets, but do not evidence that the co-movement increases in periods of financial distress. I also analyze the transmission of volatility between the two markets. The results do not support the hypothesis that volatility propagation surges during financial distress periods. On the contrary, for some cases, the data suggests that the lead-lag relationships between the two markets volatility are stronger during stable periods.
Keywords: G13; G14; G15; G47; 330; CDS markets; credit risk; contagion; Merton's model; price discovery